A Fast and Robust Dual-label Nonradioactive Oligonucleotide Ligation Assay for Detection of Factor V Leiden - Chakravarty, Anders; Hansen, Torben Stiig; Hørder, Mogens; Kristensen, Søren Risom (Thrombosis and Haemostasis, 1997)
Activated protein C resistance is in almost all cases caused by the factor V Leiden mutation (FV:R506Q). Due to the high prevalence and clinical significance of the mutation reliable methods suited for processing large sets of samples are in demand. We here present the oligonucleotide ligation assay (OLA) with lanthanide labeled oligonucleotides for the detection of FV Leiden. The assay is based on time resolved fluorescence measurement of lanthanide labeled oligonucleotides (DELFIA: Delayed Enhanced Lanthanide Fluorescence Immuno Assay) and on the specificity of T-4 DNA Ligase to join two adjacent oligonucleotides only when the two are complementary to the PCR template at the ligation junction. The Europium/Samarium fluorescence pattern is specific for each of the three genotypes (G/G, G/A, A/A) and clearly separates the three genotypes. By using a wildtype probe (Samarium labeled) and a mutant-specific probe (Europium labeled) simultaneously an internal control of the assay is included in each reaction. The assay is simple to perform, can be partly automated and is ideal for processing large sets of samples.